Three-Dimensional Culture of Human Dental Pulp Tissue: A Preliminary Experimental In Vitro Model for Regenerative Endodontic Procedures - Saber Khazaei; Rezvan Amirkhani; Azam Bozorgi; Mozafar Khazaei (Dental Hypotheses, 2023)
Introduction: Dental pulp regeneration is fundamental in dentistry and endodontics; however, few in vitro experimental models are available to study its biological process. This study aimed to develop a three-dimensional (3D) culture model of human dental pulp-like tissue mimicking the possible complexity of human pulp tissue. This new and innovative human-like tissue model could be used for testing drugs and materials, particularly those involved in regenerative endodontics. Methods: Vital pulp tissue samples were obtained from human third molars (n = 4) immediately after extraction and cultured in a 3D fibrin matrix to create a sustainable ex vivo experimental model. The angiogenesis degrees and the nitric oxide levels were evaluated following the culture of pulp-like tissues in the fibrin matrix for 21 days. The expression of Transforming growth factor- beta (TGF-β1), TGF-β2, TGF-β3, and their relevant receptors, tumor necrosis factor (TNF) and vascular endothelial growth factor A (VEGFA) was evaluated using a reverse transcription polymerase chain reaction (RT-PCR) method. Results: Pulp tissue angiogenesis was initiated, and completed on days 7 and 21, and pulp-like tissue cells expressed TGF-β1, TGF-β2, TGF-β3, and their relevant receptors, TNF and VEGFA. Conclusion: This model provided a precise observation of dental pulp angiogenesis at early stages.